Identificando barreiras de gênero nas aulas de futsal - Pereira, Paloma (Brasil, 2024)
The aim of this study is to analyze the participation of girls in practical classes in the sport of futsal during Physical Education classes. Especially with regard to gender issues, during experiences in the Institutional Teaching Initiation Program (PIBID) in the school environment. Considering the place of women in soccer, we sought to collect data in a qualitative way, using a questionnaire containing questions about girls' participation in futsal, their experiences and their inclusion in the sport, and whether there are gender differences in the practice of futsal in the school environment. The study was carried out with 10 girls from the 5th grade classes at the Gentil Belém State School located in the municipality of Parintins, Amazonas. The results show that the students enjoy and practice futsal at school, but face discrimination and prejudice, and there is little interaction between the two. However, outside the school environment, they rarely have the opportunity to practise the sport. The research reveals that teachers separate boys and girls in PE classes, and the preference is for classes to be held separately rather than together. The research showed that the lack of inclusion and unequal treatment were factors that contributed to girls' withdrawal from sport.